Análise da especificação de materiais e componentes construtivos no processo de projeto de construções metálicas - Fernanda Gomes Jardim (2010)
The current scenario of high competitiveness in civil construction, coupled with increasing client demands, has lead to a constant tightening of deadlines, improvement of efficiency, an increase in productivity and better quality of projects. The adoption of new technologies and the implementation of constructive rationalization through the use of steel construction and compatible associated systems present a potentially interesting alternative in building, due to its lightness, time efficiency, waste reduction and optimized use of space. However, it is necessary to maintain a systemic view of the entire process, as well as to have a good knowledge of the materials involved so that steel construction may be used to its highest potential, and that all materials specifications and constructive components may be anticipated at design level. Aspects such as modulation, standardization and detailing of ligaments in the association of materials should be considered from the initial concept of architectural design and demand active participation of all professionals including suppliers involved in the construction process, and a project management with experience in steel construction. This study aims to analyze and present a diagnosis of the materials specification process as well as the constructive components in the design process of steel constructions. To that end, a series of interviews were done with professionals working in architectural design and structural calculations firms, as well as experts in metallic structures and suppliers commonly associated with this type of construction, all of whom representative of the Belo Horizonte area. A case study of a finished project was also presented, with a view to illustrating the reality of the market. The answers provided by designers and suppliers were analyzed and aspects such as the particularities of steel construction designs, definition of both the structural and constructive systems (materials and components) and the integration of the different agents involved in the design process were also identified. Questions such as the late selection of the metallic structure system, the lack of time spent on planning and problems related to details and wrong specifications were some of the problems identified in this research. The study concludes that the design process and the specification of materials and constructive components in steel construction are still inefficient in some aspects and may limit the use of metallic structure systems. This study hopes to contribute to the improvement in quality of building projects which make use of this type of structure.